Acción del plaguicida organofosforado clorpirifos sobre la carcinogénesis mamaria - Ventura, Clara (2014)
In the last years, environmental pollutants have become an issue of serious\nconcern in relation to human health problems. Breast cancer risk has been related to\npollutants exposure because of many toxicants may act as endocrine disruptor by\naffecting the normal physiology of the mammary gland. In our work, we have\ndemonstrated that low doses of the organophosphorus pesticide chlorpyrifos (CPF)\ninduce MCF-7 breast cancer cells proliferation mediated by estrogen receptor action.\nHigher doses of the pesticide conduce to a diminished clonogenicity through an\nincrement of reactive oxygen species (ROS) and ERK1/2 phosphorylation. Therefore,\nCPF modified mammary gland structure in rats, induced the appearance of benign\nlesions as adenosis or florid ductal hyperplasia. CPF also affected the endocrine system\nby changing steroid and pituitary hormone levels and steroidogenesis. Finally, we have\nfound that CPF predisposes to breast cancer promotion in an experimental model in rats.\nOur results provide new findings on the mechanism of action induced by the\norganophosphorus CPF in breast cancer cells where the pesticide interferes in redox\nbalance, activates MAPKs pathways, affects the endocrine system and mammary gland\nhistology structure. Altogether, our results point to CPF as a new factor risk for breast\ncancer.